2016
DOI: 10.18632/oncotarget.12581
|View full text |Cite
|
Sign up to set email alerts
|

IL27 controls skin tumorigenesis via accumulation of ETAR-positive CD11b cells in the pre-malignant skin

Abstract: Establishment of a permissive pre-malignant niche in concert with mutant stem are key triggers to initiate skin carcinogenesis. An understudied area of research is finding upstream regulators of both these triggers. IL27, a pleiotropic cytokine with both pro- and anti-inflammatory properties, was found to be a key regulator of both. Two step skin carcinogenesis model and K15-KRASG12D mouse model were used to understand the role of IL27 in skin tumors. CD11b−/− mice and small-molecule of ETAR signaling (ZD4054)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…The following antibodies were used: primary antibody against PD-L1 (Proteintech 17952 and 66248, GeneTex GTX31308), pan-AKT (Cell Signaling Technology 4685), phosphor-AKT S473 (Abcam ab81283, Cell Signaling Technology 9271), GSK3β (Cell Signaling Technology 12456), phosphor-GSK3β Ser9 (Cell Signaling Technology 5558), WSX1 (Thermo Fisher PA5-96963), β-catenin (Cell Signaling Technology 8480), phosphor-β-catenin Ser33/37/Thr41 (Cell Signaling Technology 9561), PTEN (Cell Signaling Technology 9188), phospho-TSC2 Thr1462 (Cell Signaling Technology 3617), TSC2 (Cell Signaling Technology 4308), PI3K-p85 (Cell Signaling Technology 4292), PI3K-p110α (Cell Signaling Technology 4255), PI3K-p110δ (Cell Signaling Technology 34050), FLAG (Cell Signaling Technology 2368), Ub (Santa Cruz Biotechnology sc-8017), and WSX1 (clone 237, Monoclonal Antibodies Core Facility at MD Anderson Cancer Center) 74 . PerCP/Cyanine5.5 anti-mouse CD3 (BioLegend 100328), V450 anti-mouse CD8a (Tonbo 75-0081), FITC anti-mouse CD4 (BioLegend 100405), V450 anti-mouse NK1.1 (BD biosciences 560524), PE/Cy7 anti-mouse PD-1 (BioLegend 109109), PE anti-mouse CTLA-4 (BioLegend 106306), PE/Cy7 anti-mouse LAG-3 (BioLegend 125225), PE anti-mouse Tim3 (BioLegend 134009), PE anti-mouse granzyme B (ebioscience 12-8898-80), PE anti-mouse Ki67 (BioLegend 652404), PE anti-mouse perforin (ebioscience 12-9392-82), PE anti-human CD3 (BioLegend 300308), PE/Cy7 anti-human PD-1 (BioLegend 367414), APC anti-mouse TOX (Miltenyi Biotec 130-118-335), APC anti-mouse IFN-γ (ebioscience 17-7311-82), PE anti-mouse IL-2 (BioLegend 503808), PE anti-human WSX1 (R&D FAB14791P), and HRP anti-human/mouse GAPDH (Proteintech HRP-6000).…”
Section: Methodsmentioning
confidence: 99%
“…The following antibodies were used: primary antibody against PD-L1 (Proteintech 17952 and 66248, GeneTex GTX31308), pan-AKT (Cell Signaling Technology 4685), phosphor-AKT S473 (Abcam ab81283, Cell Signaling Technology 9271), GSK3β (Cell Signaling Technology 12456), phosphor-GSK3β Ser9 (Cell Signaling Technology 5558), WSX1 (Thermo Fisher PA5-96963), β-catenin (Cell Signaling Technology 8480), phosphor-β-catenin Ser33/37/Thr41 (Cell Signaling Technology 9561), PTEN (Cell Signaling Technology 9188), phospho-TSC2 Thr1462 (Cell Signaling Technology 3617), TSC2 (Cell Signaling Technology 4308), PI3K-p85 (Cell Signaling Technology 4292), PI3K-p110α (Cell Signaling Technology 4255), PI3K-p110δ (Cell Signaling Technology 34050), FLAG (Cell Signaling Technology 2368), Ub (Santa Cruz Biotechnology sc-8017), and WSX1 (clone 237, Monoclonal Antibodies Core Facility at MD Anderson Cancer Center) 74 . PerCP/Cyanine5.5 anti-mouse CD3 (BioLegend 100328), V450 anti-mouse CD8a (Tonbo 75-0081), FITC anti-mouse CD4 (BioLegend 100405), V450 anti-mouse NK1.1 (BD biosciences 560524), PE/Cy7 anti-mouse PD-1 (BioLegend 109109), PE anti-mouse CTLA-4 (BioLegend 106306), PE/Cy7 anti-mouse LAG-3 (BioLegend 125225), PE anti-mouse Tim3 (BioLegend 134009), PE anti-mouse granzyme B (ebioscience 12-8898-80), PE anti-mouse Ki67 (BioLegend 652404), PE anti-mouse perforin (ebioscience 12-9392-82), PE anti-human CD3 (BioLegend 300308), PE/Cy7 anti-human PD-1 (BioLegend 367414), APC anti-mouse TOX (Miltenyi Biotec 130-118-335), APC anti-mouse IFN-γ (ebioscience 17-7311-82), PE anti-mouse IL-2 (BioLegend 503808), PE anti-human WSX1 (R&D FAB14791P), and HRP anti-human/mouse GAPDH (Proteintech HRP-6000).…”
Section: Methodsmentioning
confidence: 99%
“…IL-27 induced CD11b cells with endothelin A receptor (ETAR)-positive phenotype. Thus, in SCC patients, Dibra et al showed that IL-27RA-positive cells in the tumor stroma are correlated with tumor de-differentiation (69).…”
Section: Non-melanoma Tumors: Squamous Cell and Basal Cell Skin Carcimentioning
confidence: 99%
“…In a previous research conducted by Dibra et al [ 27 ], IL-27 was shown to play an unrecognizable role in promoting papilloma formation, which disrupted epithelial stem cell homeostasis/maintenance. A follow-up study demonstrated that [ 28 ], in a K15-KRASG12D mouse model, IL-27 accelerated the accumulation of endothelin A receptor-positive CD11b cells, a novel category of protumor inflammatory cells, thus establishing a premalignant niche and expanding the mutation of stem cells. In patients with squamous cell carcinoma, the distribution of IL-27 receptor subunit alpha-positive cells in the stroma was shown to be closely correlated to tumor dedifferentiation.…”
Section: Discussionmentioning
confidence: 99%